Why can't you unscramble an egg? : and other not such dumb questions about matter - Cobb, Vicki; Enik, Ted (New York : Lodestar Books, 1990)
Answers nine questions about matter, such as why does an ice cube float?, how much does air weigh?, how does wood burn? and other concepts about the nature of matter.
Includes index.
School Library Journal.
4.2
4.2
3-6.
3-6
Keywords: Matter -- Composition -- Juvenile literature; Matter; Questions and answers; Matter; Questions and answers